Lung function in relation to six-minute walk test in pulmonary hypertension - Amir Farkhooy; Michaela Bellocchia; Hans Hedenström; Daniela Libertucci; Caterina Bucca; Christer Janson; Paolo Solidoro; Andrei Malinovschi (European Clinical Respiratory Journal, 2020)
Background: Pulmonary hypertension (PH) is a progressive disorder of the pulmonary circulation, associated with diverse medical conditions. Exercise limitation is the most prominent symptom in PH. Exercise capacity, commonly assessed through a six-minute walk test (6MWT), correlates with both functional status and survival in PH. Few studies have analysed the relation between respiratory function and exercise limitation. Therefore, we investigated the relationship between resting pulmonary function, exercise capacity, and exertional desaturation, assessed through the 6MWT, in unselected PH patients. Methods: Fifty consecutive patients with PH diagnosis, referred for pulmonary function testing (lung volume, spirometry, and diffusing capacity for carbon monoxide (DLCO)) and 6MWT, were recruited at Molinette University Hospital, Turin. Results: The majority of the patients (54%) had PH due to left heart disease. Airway obstruction (FEV1/VC-ratio < 0.7) was found in 46% of the patients and they performed significantly worse in the 6MWT than unobstructed patients (307 m vs. 377 m). Patients with PH due to left heart disease also performed significantly poorer 6MWT when airway obstruction was present (305 m vs. 389 m). Twenty-two patients (44%) presented exertional desaturation upon 6MWT. Lower DLCO divided by the alveolar volume (DLCO/VA), FEV1/VC-ratios and resting PaO2-values were significantly correlated with exertional desaturation after adjustments for age, sex, BMI, and smoking habits. DLCO/VA was the main determinant of exertional desaturation in a stepwise regression model. Conclusions: Spirometric parameters of airway obstruction were related to walk distance and exercise-induced desaturation in PH patients. This suggests a place for spirometry in clinical monitoring of PH patients.